A Novel Innate Immune-Enhancement Strategy Combined with IVIG Rescues Mice from Fatal Staphylococcus aureus Septicemia - Gowrisankar Rajam; Gabrielle M. Hammons; George M. Carlone; Jacquelyn S. Sampson; Edwin W. Ades (International Journal of Microbiology)
Staphylococcus aureus (SA) is a major community-acquired pathogen. The emergence of drug-resistant strains like, methicillin-resistant SA (MRSA), poses stiff challenges to therapeutic intervention. Passive immune-therapy with specific antibodies is being actively examined to treat fulminant infections with limited success. In this study, we demonstrate that P4, a 28-amino acid peptide, derived from pneumococcal surface adhesin A along with pathogen-specific antibody (IVIG; P4 therapy) is successful in enhancing the opsonophagocytic killing (OPK) of S. aureus in vitro. We questioned if it is possible to expand P4 therapy to treat staphylococcal infections in vivo. P4 therapy in combination with IVIG rescued 7/10 morbidly ill S. aureus-infected mice while only 2/10 survived in the control group.